Sustained Visual Field Recovery Following Autologous Stem Cells and Exosomes Based Therapy in Recurrent Optic Neuritis – A Case Report: Doi: 10.36351/pjo.v42i1.2272 - Huma Ali Mirza; Muhammad Irfan Karamat; Zaigham Abbas; Kashif Jahangir (Pakistan Journal of Ophthalmology, 2025)
A 40-year-old male had recurrent episodes of optic neuritis. Best-corrected visual acuity was evaluated and Humphrey Visual Field analysis was done before and after treatment. Treatment consisted of three weekly cycles of intravenous platelet-rich plasma combined with exosomes, followed one week later by bilateral posterior sub-tenon, retrobulbar, and intravenous injections of blood-derived mononuclear cells.At 3 months of follow-up, Humphrey visual fields showed significant improvement. The patient reported subjective improvement in visual acuity. No further relapses occurred, and no steroid or other systemic therapy was required during the follow-up period.The combined approach of using autologous PRP, exosomes, and hematopoietic stem cell therapy may cause sustained visual field recovery in recurrent optic neuritis refractory to corticosteroids.